Rapid Progression of a Urinary Bladder Leiomyosarcoma: Report of a Case - Toru Yamada; Shingo Nagai; Yusuke Kanimoto (Case Reports in Urology)
The case we report shows rapid progression and a very poor prognosis only for a month that differs from the clinical course reported in the literature. An 83-year-old man was referred to our hospital for macroscopic hematuria. Computed tomography (CT) revealed a large bladder tumor measuring 4 cm × 3 cm and magnetic resonance imaging revealed extravesical invasion and pelvic wall invasion of the tumors. Chest CT and bone scintigraphy revealed no evidence of distant visceral metastases, and a clinical diagnosis of T4N0M0 was made. Transurethral resection of the bladder tumor (TUR-BT) was performed for histopathological diagnosis 18 days after admission, and no further adjuvant treatment was given. At 15 days after TUR-BT, the patient's clinical status worsened with symptoms of exertional dyspnea. CT showed multiple metastatic lesions in the lung, liver, and retroperitoneal lymphadenopathy. The patient died 2 days later and underwent autopsy. A final histopathological diagnosis of leiomyosarcoma was made based on immunohistochemical staining.